Nocturnal road traffic noise assessment and sleep research: The usefulness of different timeframes and in- and outdoor noise measurements - Pirrera, Sandra; De Valck, Elke; Cluydts, Raymond (Applied acoustics, 2011)
In this paper, we investigated the procedure of noise assessment in the study of nocturnal noise exposure during sleep in the home situation. The use of two different timeframes (fixed from 11 PM to 07 AM versus personal “Time in Bed” period) was explored as well as the relation between indoor and outdoor noise levels and between the actual and estimated noise levels. Noise recordings were performed inside and outside the bedroom of 24 subjects living in high density road traffic noise areas in the Brussels’ Capital Region during seven consecutive days. Indoor and outdoor noise indicators L Aeq, L Amax and individual noise events were analysed. Subjects completed a daily sleep log in which the Time in Bed period was assessed. The results indicate that, for outdoor noise assessment, the use of an average L Aeq might not be sufficient to reflect well the noise levels during the sleep period. For indoor measurements, significant differences were found in the comparison between both timeframes ( L Aeq: T = 16; p < .001). Considering the relation between indoor and outdoor measurements, low correlations ( r = .49; p < .001) were found even when the location of the bedroom as a mediating factor was accounted for (street side; r = .52; p < .001). Therefore, from our study, caution is needed when relying on outdoor noise measurements for the evaluation of sleep disturbances. Furthermore, one needs to be aware of the weak correspondence between indoor and outdoor noise levels in the discussion of what a harmonized noise indicator for the evaluation of noise exposure and sleep disturbances should consist of.